Endobronchial Ultrasound-guided Sampling of Centrally Located Intrapulmonary Tumors Provides Suitable Material for Diagnostic and Molecular Testing. Issue 2 (13th April 2023) - Rai, Hem; Graham, Emma; Ghoshal, Avik; McDill, Helen; Hassan, Maged; Nicholson, Thomas; Taylor, Lindsey; Corcoran, John; Howell, Timothy; Daneshvar, Cyrus
Abstract : Background: Curvilinear endobronchial ultrasound transbronchial needle aspiration (EBUS-TBNA) is a key diagnostic and staging procedure for patients with suspected lung cancer. However, sampling centrally located intrapulmonary tumors is feasible but less well established. Methods: We retrospectively evaluated the diagnostic utility of EBUS-TBNA in patients who underwent sampling of centrally located intrapulmonary tumors. Diagnostic accuracy, sample suitability for molecular testing, and complications were assessed. Results: Between January 2015 and April 2021, 102 EBUS-TBNA procedures sampled centrally located intrapulmonary tumors in 99 patients. The median age was 70 [interquartile range, 63 to 75] years and 51% (51/99) were male. The commonest site was the right upper lobe (n=42/99; 42%). The median tumor size was 29 [interquartile range, 21 to 35] mm. The diagnostic yield was 88/102 (86%) with a false negative rate of 14% (14/102). In addition to intrapulmonary tumor sampling, lymph nodes were sampled in 65/102 procedures and 30/65(46%) were positive for lung cancer. Cancer was diagnosed in 87/99 (88%) cases. When requested, molecular testing was adequate in ≥94% of samples. Complications included minor bleeding in 6/102 (6%) with 2 requiring cold saline instillation, desaturation in 1/102 (1%), and tachycardia in 1/102(1%). One procedure was abandoned due to patient tachycardia. Delayed complications occurred in 1 patient who was hospitalized ≤7 days with pneumonia. Conclusion: EBUS-TBNA sampling of centrally located intrapulmonary tumors provides similar diagnostic accuracy to lymph node sampling, provides suitable material for molecular testing, and has a low complication rate.